1999
DOI: 10.1046/j.1365-3024.1999.00244.x
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Leishmania major in a CBA mouse model of infection: role of adjuvants and mechanism of protection

Abstract: Gp63 is a major surface protein of Leishmania promastigotes. Its protective efficacy has been tested in several experimental models using different mouse strains, gp63 forms, adjuvants and routes of immunization, giving rise to conflicting results. This investigation was designed to determine whether these discrepancies could be ascribed to differing experimental procedures, and to compare gp63-induced protection with that achieved using live promastigotes. Preliminary experiments demonstrated that gp63 was an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 34 publications
2
31
0
1
Order By: Relevance
“…This study extends the data obtained with the mouse and dog models (2,72,82,83,114) and provides a basis for further human trials. However, because delayed-type hypersensitivity was not predictive of protection in this monkey model, the value of delayed-type hypersensitivity as a surrogate marker of protection in humans needs to be reassessed.…”
Section: Killed Vaccinessupporting
confidence: 76%
See 1 more Smart Citation
“…This study extends the data obtained with the mouse and dog models (2,72,82,83,114) and provides a basis for further human trials. However, because delayed-type hypersensitivity was not predictive of protection in this monkey model, the value of delayed-type hypersensitivity as a surrogate marker of protection in humans needs to be reassessed.…”
Section: Killed Vaccinessupporting
confidence: 76%
“…Such immunization will also deliver many more parasite antigens than the limited number possible with subunit or recombinant antigens. Summarizing a large amount of experimental evidence, Rivier et al (114) concluded that injection of attenuated organisms achieved better protection than any method involving recombinant gp63 as test antigen delivered with a variety of adjuvants and delivery systems. If this conclusion is shown to be generally applicable to other vaccine candidates, the prospect of using attenuated Leishmania vaccines in preference to subunit or recombinant approaches will gain favor.…”
Section: Live-attenuated Vaccinesmentioning
confidence: 99%
“…The metalloprotease glycoprotein 63 (GP63) is the major surface glycoprotein of Leishmania and is considered an important virulence factor and a strong immunogen (168). The gene is arranged as a tandemly repeated unit, and both the intra-and intergenic regions have been used for typing by RFLP analysis.…”
Section: Gp63mentioning
confidence: 99%
“…In addition, higher levels of parasite Ags are delivered at the site of the infection than when using subunit vaccines. Indeed, vaccination with avirulent organisms achieved better protection than classical immunizations with selected Ags whatever the adjuvants and delivery systems used (21). Several vaccination strategies that lead to obtaining live attenuated organisms have been attempted, including long-term in vitro cultures (22), selection for temperature sensitivity (23), chemical mutagenesis (24), and parasite culture under drug pressure (25).…”
mentioning
confidence: 99%